PELAYANAN PUBLIK BERBASIS PELAYANAN PRIMA DI UNIT TRANSFUSI DARAH PALANG MERAH INDONESIA (PMI) KOTA SURABAYA - Dharmawan, Awan; Rukin; zulharman (Journal of Law and Administrative Science, 2025)
This research aims to see how Excellent service-based public services are implemented at UTD PMI Surabaya City as mandated by law No. 25 of 2009 concerning Public Services as well as the mandate and Regulation of the Minister of Health (PMK) of the Republic of Indonesia Number 83 of 2014 concerning Blood Transfusion Units, Banks Blood. and Blood Transfusion Services Network. The research design used qualitative methods and a descriptive approach was used (Sugiyono, 2017), to answer the research problem, a theoretical approach to the characteristics of excellent service was used (Wijaya, 2022). The research results showed that the theoretical dimensions existed, namely: appearance, politeness and friendliness, willingness to serve, knowledge and expertise, punctuality and promise, honesty and trust, efficiency, legal certainty, openness are all in accordance with existing theoretical indicators. Recommendations for UTD PMI Surabaya City must be additional human resources so that public services can be more optimal, especially for managing patient and non-patient visitor traffic, in the future.